Abdominal splanchnic haemodynamics in a canine normovolaemic anaemia model and uncomplicated canine babesiosis : a comparative doppler study - Kirberger, Robert M. (University of Pretoria, 2013)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2005.